2010
DOI: 10.1074/jbc.m110.113100
|View full text |Cite
|
Sign up to set email alerts
|

Trm112p Is a 15-kDa Zinc Finger Protein Essential for the Activity of Two tRNA and One Protein Methyltransferases in Yeast

Abstract: The degenerate base at position 34 of the tRNA anticodon is the target of numerous modification enzymes. In Saccharomyces cerevisiae, five tRNAs exhibit a complex modification of uridine 34 ( . An mtq2-0 trm9-0 strain exhibits a synthetic growth defect, thus revealing the existence of an unexpected link between tRNA anticodon modification and termination of translation. Trm112p is associated with other partners involved in ribosome biogenesis and chromatin remodeling, suggesting that it has additional roles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
88
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(94 citation statements)
references
References 53 publications
6
88
0
Order By: Relevance
“…17 Inactivation of the other S. cerevisiae Elongator genes encoding Elp1-Elp2p and Elp4-Elp6p displayed identical phenotypes as the elp3 null mutant including the tRNA modification defect. 17,18 This observation suggested that the Elongator complex is required for synthesis of the first step, an intermediate likely to be 5-carboxymethyluridine (cm 5 U) [19][20][21][22][23] , in formation of mcm 5 U, mcm 5 s 2 U, ncm 5 U and ncm 5 U m at U 34 in tRNA (Fig. 1).…”
Section: 15mentioning
confidence: 99%
See 1 more Smart Citation
“…17 Inactivation of the other S. cerevisiae Elongator genes encoding Elp1-Elp2p and Elp4-Elp6p displayed identical phenotypes as the elp3 null mutant including the tRNA modification defect. 17,18 This observation suggested that the Elongator complex is required for synthesis of the first step, an intermediate likely to be 5-carboxymethyluridine (cm 5 U) [19][20][21][22][23] , in formation of mcm 5 U, mcm 5 s 2 U, ncm 5 U and ncm 5 U m at U 34 in tRNA (Fig. 1).…”
Section: 15mentioning
confidence: 99%
“…2). [20][21][22][23]52,53 Other than being a subunit required for Trm9p activity, Trm112p is also a subunit required for the activity of 3 other methyltransferases, the tRNA methyltransferase Trm11p forming m 2 G 10 in tRNA, the ribosomal methyl transferase Bud23p methylating G1575 in 18S rRNA 54 and Mtq2p methylating the release factor eRF1.…”
mentioning
confidence: 99%
“…Trm112 is a small zinc finger protein of 15 kDa which acts as a coactivator of several class I S-adenosyl-L-methionine (SAM)-dependent MTases (15,32,36,49,58). To date, Trm112 is known to interact with, and to activate, three MTases, namely, Mtq2, Trm9, and Trm11, all related to ribosome function.…”
mentioning
confidence: 99%
“…Interestingly, PaOrf2 is unable to cleave its substrates when the wobble uridine methylase Trm9 (part of a complex with Trm112) is lacking (Klassen et al 2008a). Since Trm9-Trm112 catalyzes the last step of mcm 5 /mcm 5 s 2 biosynthesis (Kalhor and Clarke 2003;Mazauric et al 2010;Chen et al 2011), and trm9 mutants accumulate ncm 5 s 2 (5-carbamoylmethyl-2-thiouridine) instead of mcm 5 s 2 (Chen et al 2011), it appears that this moiety is inhibitory for PaT.…”
Section: Introductionmentioning
confidence: 99%